A cocktail of usual and unusual presentation of cutaneous tumors – A case series - Maroo, Vandana; Singha Roy, Debajyoti; Mukherjee, Sanghamitra; Mandal, Meghadipa (Asian Journal of Medical Sciences, 2024)
Epidermal cutaneous tumors represent an enormous group of tumors, which can be classified as both benign and malignant, and primary and secondary. In this case series, there are six cases of such tumors encountered in a health-care center of Eastern India. The histopathological examination IS mainstay of reporting in some cases; however, other cases do require a supplementary immunohistochemistry or electron microscopy for confirmatory diagnosis. The childhood lesions should not be ignored, as it may present as metastasis many years later.